Catalytic pyrolysis of biomass with char modified by cathode materials of spent lithium-ion batteries for tar reduction and syngas production. (15th May 2022) - Shen, Yafei
Graphical abstract: Highlights: The char modified by the spent cathode was used for catalytic biomass pyrolysis. The char catalyst had hierarchical pore structure and large surface area. The apparent activation energy of rice husk pyrolysis reduced from 79 to 66 kJ/mol. The acids and phenols contents decreased from 20.6% to 3.6% and from 29.4% to 8.0%. The char catalysts converted oxygenates to small-molecule hydrocarbons and gases. Abstract: The char modified by the battery cathode material was studied for catalytic pyrolysis of rice husk (RH). Compared to the direct mixing, the addition of cathode material to char by the impregnation was more favorable to synthesize the lignin char catalyst (i.e. char 1) with hierarchical pore structure and larger specific surface area. The char 1 decreased the Ea of the RH pyrolysis from 79 kJ/mol to 66 kJ/mol. The char 1 decreased the yield of liquid product from 23.2% to 12.3% and increased the yield of gas product from 35.2% to 52.2%. The char 1 decreased the contents of acids from 20.6% to 3.6% and phenols (tar surrogates) from 29.4% to 8.0%. The increase of hydrocarbons and CO2 indicated that the char catalysts had high catalytic reactivity in converting the oxygenated components (e.g., sugars, furans, acids, phenols) into light hydrocarbons (e.g., alkanes, aromatics) and micro-molecular gases (e.g., CO2, H2 ).